2023
DOI: 10.1080/0886022x.2023.2238825
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid is associated with chronic kidney disease in elderly Chinese patients with diabetes

Qing Zhou,
Sisi Ke,
Yaqiong Yan
et al.

Abstract: Background The relationship between hyperuricemia and chronic kidney disease (CKD) has been investigated extensively. However, studies on elderly individuals are still limited. Moreover, there is no consensus on whether hyperuricemia or elevated serum uric acid (SUA) within the normal range is correlated with the new onset of CKD and whether there are differences between males and females. Methods We included 39039 elderly diabetic patients without CKD at baseline from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The rationale for lowering serum urate concentrations to prevent CKD and its progression is primarily based on both biologic plausibility and findings from observational studies. [23][24][25] There are several biologic pathways through which hyperuricemia may induce early kidney injury, including induction of a specific afferent arteriolar vasculopathy, promotion of endothelial dysfunction through nitric oxide inhibition, and activation of the renin-angiotensin-aldosterone system. 26 Observational studies have found strong associations between hyperuricemia -40 -20 0 and the risk of new-onset kidney disease, 27 while pooled analysis of clinical trial data has suggested that lowering serum urate concentrations resulted in few major kidney events.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for lowering serum urate concentrations to prevent CKD and its progression is primarily based on both biologic plausibility and findings from observational studies. [23][24][25] There are several biologic pathways through which hyperuricemia may induce early kidney injury, including induction of a specific afferent arteriolar vasculopathy, promotion of endothelial dysfunction through nitric oxide inhibition, and activation of the renin-angiotensin-aldosterone system. 26 Observational studies have found strong associations between hyperuricemia -40 -20 0 and the risk of new-onset kidney disease, 27 while pooled analysis of clinical trial data has suggested that lowering serum urate concentrations resulted in few major kidney events.…”
Section: Discussionmentioning
confidence: 99%
“…The escalating incidence of chronic kidney disease (CKD) in recent years has raised considerable concerns, notably due to its substantial impact on patient mortality rates, rendering it a critical area of study. Given that the importance of UA has been highlighted for both diabetic[ 2 ] and non-diabetic patients[ 3 ], the article endeavors to offer a more comprehensive perspective on the risk factors for CKD. It extends beyond the traditional boundaries of research by incorporating lifestyle and inflammation markers into the analysis, and furthermore, employs cutting-edge machine learning methods, thereby presenting an innovative approach to identifying subjects with abnormal renal function.…”
Section: To the Editormentioning
confidence: 99%